Regulation of Erythropoietin Expression in High-Altitude Populations in Mexico: A Comprehensive Study - Fransisco Guezada; Jaime Florez-Diaz (Sriwijaya Journal of Internal Medicine, 2023)
Introduction: High altitude exposure triggers physiological responses to compensate for reduced oxygen availability. Erythropoietin (EPO), a key hormone regulating red blood cell production, plays a crucial role in this adaptation. This study investigated the regulation of EPO expression in Mexican populations residing at high altitudes, examining the influence of genetic factors, altitude levels, and physiological parameters. Methods: A cross-sectional study was conducted involving 400 healthy adults residing at varying altitudes in Mexico (2,240 m to 3,500 m above sea level). Participants were stratified by altitude and genotyped for EPO gene polymorphisms. Serum EPO levels, hematological parameters (hemoglobin, hematocrit, red blood cell count), and oxygen saturation (SpO2) were measured. Statistical analyses were performed to assess associations between EPO levels, genetic variants, altitude, and physiological parameters. Results: Serum EPO levels were significantly elevated in high-altitude residents compared to those residing at lower altitudes (p<0.001). Specific EPO gene polymorphisms were associated with variations in EPO levels (p=0.025). Hemoglobin, hematocrit, and red blood cell count showed a positive correlation with altitude and EPO levels (p<0.001). SpO2 negatively correlated with altitude and EPO levels (p<0.001). Conclusion: This study demonstrates the complex interplay of genetic and environmental factors in regulating EPO expression in high-altitude populations in Mexico. Our findings highlight the adaptive mechanisms crucial for maintaining oxygen homeostasis at high altitudes and provide insights into the individual variability in response to hypoxic conditions.